2016
DOI: 10.3767/003158516x690934
|View full text |Cite
|
Sign up to set email alerts
|

Novel fungi from an ancient niche: cercosporoid and related sexual morphs on ferns

Abstract: The fern flora of the world (Pteridophyta) has direct evolutionary links with the earliest vascular plants that appeared in the late Devonian. Knowing the mycobiota associated to this group of plants is critical for a full understanding of the Fungi. Nevertheless, perhaps because of the minor economic significance of ferns, this niche remains relatively neglected by mycologists. Cercosporoid fungi represent a large assemblage of fungi belonging to the Mycosphaerellaceae and Teratosphaeriaceae (Ascomycota) havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…Based on LSU DNA sequence data Phaeophleospora eucalypticola is identical (100 %) (818/818) to P. hymenocallidicola (CPC 25014; GenBank KR476772.1) and 99 % (846/849) similar to P. eugeniae (CPC 15159; GenBank FJ493207.1) ( Crous et al 2015a ). Based on ITS sequence data it is 94 % (453/482) similar to P. pteridivora (COAD 1182; GenBank KT037547.1), though the latter species has conidia that are subcylindrical, curved to sinuous, 70–107 × 2–3 μm, 6–9-septate ( Guatimosim et al 2016 ). The ITS sequence of P. eucalypticola is similar to numerous sequences in GenBank labelled as ‘ Mycosphaerella sp.…”
mentioning
confidence: 99%
“…Based on LSU DNA sequence data Phaeophleospora eucalypticola is identical (100 %) (818/818) to P. hymenocallidicola (CPC 25014; GenBank KR476772.1) and 99 % (846/849) similar to P. eugeniae (CPC 15159; GenBank FJ493207.1) ( Crous et al 2015a ). Based on ITS sequence data it is 94 % (453/482) similar to P. pteridivora (COAD 1182; GenBank KT037547.1), though the latter species has conidia that are subcylindrical, curved to sinuous, 70–107 × 2–3 μm, 6–9-septate ( Guatimosim et al 2016 ). The ITS sequence of P. eucalypticola is similar to numerous sequences in GenBank labelled as ‘ Mycosphaerella sp.…”
mentioning
confidence: 99%
“…The morphology of the genus is rather heterogenous, and it is polyphyletic, as recognized in some previous studies (Crous et al, 2009;Quaedvlieg et al, 2014) and as shown in our analysis (Figure 3). In this study, we expanded the description of P. hymenocallidicola by several characters that were not observed or examined by Crous et al (2015Crous et al ( , 2016. Namely, we determined that the optimal growth temperature of the fungus is between 25 and 30°C, we observed that conidia can bud in a yeast-like fashion, and we showed that some of them have up to two septa, while a significant portion of the conidia in older colonies had larger dimensions and irregular shapes.…”
Section: (B)mentioning
confidence: 60%
“…The reaction mixture and PCR protocol were described previously by Hubka et al (2016). The PCR product purification followed the protocol The ITS rDNA region sequences for the phylogenetic analysis across the family Mycosphaerellaceae were retrieved mostly from previously published studies (Crous, Groenewald, Summerell, Wingfield, & Wingfield, 2009;Guatimosim, Schwartsburd, Barreto, & Crous, 2016;Quaedvlieg et al, 2014) and the NCBI database. The alignment was performed using the G-INS-i option implemented in MAFFT v. 7 (Katoh & Standley, 2013).…”
Section: Molecular Studies and Phylogenetic Analysismentioning
confidence: 99%
“…Cercosporoid fungi represent a very large group of plant pathogenic, leaf-spotting, economically relevant species causing diseases on a wide range of hosts, including numerous cultivated plants. In the last few decades, enormous taxonomic progress has been made by increasing application of molecular methods in capnodialean fungi, including Mycosphaerellaceae ( Crous et al 2013 , Groenewald et al 2013 , Bakhshi et al 2014 , Nguanhom et al 2015 , Guatimosim et al . 2016 , etc.).…”
Section: Introductionmentioning
confidence: 99%
“…without any asexual fructifications, are known in many currently recognised cercosporoid genera (e.g. Guatimosim et al . 2016 ).…”
Section: Introductionmentioning
confidence: 99%